Cloning and Expression of the Erwinia carotovora subsp. carotovora Gene Encoding the Low-Molecular-Weight Bacteriocin Carocin S1 - Chuang, Duen-yau; Chien, Yung-chei; Wu, Huang-Pin (Journal of Bacteriology, 2007)
Article Usage Stats Services JB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JB About JB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0021-9193 Online ISSN: 1098-5530 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JB .asm.org, visit: JB